2018
DOI: 10.1088/1361-6560/aad8eb
|View full text |Cite
|
Sign up to set email alerts
|

Geometrical structures for radiation biology research as implemented in the TOPAS-nBio toolkit

Abstract: Computational simulations, such as Monte Carlo track structure simulations, offer a powerful tool for quantitatively investigating radiation interactions within cells. The modelling of the spatial distribution of energy deposition events as well as diffusion of chemical free radical species, within realistic biological geometries, can help provide a comprehensive understanding of the effects of radiation on cells. Track structure simulations, however, generally require advanced computing skills to implement. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 72 publications
(102 reference statements)
1
36
0
Order By: Relevance
“…5, it is shown the production of the hydroxyl radical, OH * , which has an inverse behavior to that of hydrogen peroxide. Where it is observed that its production decay of this radical is approximately 80% in a time of nanoseconds, which is consistent with its half-life [9,11]. This last result shows that the hydroxyl radical "existence" time is around a few nanoseconds, which is in agreement with its half-life, as previously expressed.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…5, it is shown the production of the hydroxyl radical, OH * , which has an inverse behavior to that of hydrogen peroxide. Where it is observed that its production decay of this radical is approximately 80% in a time of nanoseconds, which is consistent with its half-life [9,11]. This last result shows that the hydroxyl radical "existence" time is around a few nanoseconds, which is in agreement with its half-life, as previously expressed.…”
Section: Resultssupporting
confidence: 87%
“…In the case that free radicals have been generated in the cell nucleus, these propagate inside it, see chemical reactions (9) and (10), having the ability to attack DNA strands.…”
Section: Formation Of Reactive Oxygen Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…The TOPAS-nBio extension is an advanced, yet userfriendly, Monte Carlo track structure simulation tool based on Geant4-DNA (9,10). It offers an extensive library of advanced biological geometries ranging from the micrometer scale (e.g., cells and organelles) down to the nanometer scale (e.g., DNA molecules and proteins) (38) to support simulation studies at the cellular and subcellular levels with the goal of furthering our understanding of radiobiological effects at the DNA (nanometer) scale (38)(39)(40). A full nucleus model was developed based on folding chromatin fibers in a fractal as indicated by Lieberman-Aiden et al (41); the chromatin conformation is consistent with a knot-free fractal globule at the megabase scale.…”
Section: Dna Modelmentioning
confidence: 99%
“…Each fiber consists of 51 nucleosomes and contains 15,150 base pairs (bp) of DNA. Chromatin fibers were folded according to a continuous 3D Hilbert space-filling curve (38) to form chromatin fiber loops and fill a voxel (Fig. 1D).…”
Section: Dna Modelmentioning
confidence: 99%